2021
DOI: 10.1152/japplphysiol.00261.2021
|View full text |Cite
|
Sign up to set email alerts
|

Sodium bicarbonate ingestion mitigates the heat-induced hyperventilation and reduction in cerebral blood velocity during exercise in the heat

Abstract: Hyperthermia during exercise in the heat causes minute ventilation (VE) to increase, which leads to reductions in arterial CO2 partial pressure (PaCO2) and cerebral blood flow. On the other hand, sodium bicarbonate ingestion reportedly results in metabolic alkalosis, leading to decreased and increased PaCO2 during prolonged exercise in a thermoneutral environment. Here, we investigated whether sodium bicarbonate ingestion suppresses heat-induced hyperventilation and the resultant hypocapnia and cerebral hypope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
0
1
0
Order By: Relevance
“…Increased body temperature triggers cutaneous vasodilation and sweating, but also causes hyperventilation which reduces arterial carbon dioxide partial pressure (PaCO 2 ) and cerebral blood flow [ 1 ]. Katagiri et al found that metabolic alkalosis produced by sodium bicarbonate ingestion reduced hyperventilation and attenuated hypocapnia-related cerebral hypoperfusion during exercise [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Increased body temperature triggers cutaneous vasodilation and sweating, but also causes hyperventilation which reduces arterial carbon dioxide partial pressure (PaCO 2 ) and cerebral blood flow [ 1 ]. Katagiri et al found that metabolic alkalosis produced by sodium bicarbonate ingestion reduced hyperventilation and attenuated hypocapnia-related cerebral hypoperfusion during exercise [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Respiratory alkalosis and the accompanying reduction in CBF have also been expected to worsen central fatigue, exercise intolerance and cognitive impairments in the heat (Hasegawa & Cheung, 2013). An emerging focus has thus centred on exploring ways of attenuating or offsetting the heat-induced hyperventilation, for example through voluntary suppression of ventilation (Tsuji et al, 2015) or sodium bicarbonate ingestion (Katagiri et al, 2021). Surprisingly, however, most studies have failed to demonstrate any benefit of maintaining eucapnia in hyperthermia, aside from the observation that the CBF is restored.…”
Section: Introductionmentioning
confidence: 99%
“…In these two studies, the placebo group ingested sodium chloride to match the sodium content of the two conditions, as they were investigating the buffering capacity of the supplement and not its effects on fluid balance (Katagiri et al, 2023;Katagiri et al, 2021). Therefore, it is likely that any potential osmotic effects that could theoretically have aided thermoregulation, would be indistinguishable from the effects in the placebo condition.…”
Section: Sodium Citrate and Sodium Bicarbonatementioning
confidence: 99%